Repair And Rehabilitation of RCC Structures Using FRP (International Journal of Innovative Research in Engineering & Management, 2023)
This paper analyses the conditions that cause restored concrete structures to operate less well, as well as the diseases that they suffer from and the remedies that can cure them. In this work, the various surface preparation techniques widely used in Indian circumstances are discussed, along with their drawbacks. In this work, we've made an effort to talk about the characteristics, varieties, and application methods of grouts. The goal of the study is to provide the ways for fixing and rehabilitating structures that have inadequacies and flaws that call for repair. The effectiveness of a holistic system approach is examined along with the effectiveness of the already employed repair and rehabilitation techniques.
Keywords: Rehabilitation; Repair; RCC; FRP etc